2014
DOI: 10.1007/s40069-014-0075-2
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Pile–Soil Interaction under Axial and Lateral Loads

Abstract: In this paper, the analysis of a numerical study of pile-soil interaction subjected to axial and lateral loads is presented. An analysis of the composite pile-soil system was performed using the finite difference (FD) software LPILE. Two three dimensional, finite element (FE) models of pile-soil interaction have been developed using Abaqus/Cae and SAP2000 to study the effect of lateral loading on pile embedded in clay. A lateral displacement of 2 cm was applied to the top of the pile, which is embedded into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 15 publications
(10 reference statements)
0
14
0
Order By: Relevance
“…An axisymmetric model has been admitted since the piles treated are cylindrical with a circular cross-section and axially loaded (the axis of symmetry, coinciding with the pile axis) [50], [54], [55]. The limits of the investigated domain are fixed more than 3.5 times the pile length (Lp), in the vertical direction and at least 2 times the pile length in the horizontal direction (Fig.…”
Section: Iv2 Numerical Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…An axisymmetric model has been admitted since the piles treated are cylindrical with a circular cross-section and axially loaded (the axis of symmetry, coinciding with the pile axis) [50], [54], [55]. The limits of the investigated domain are fixed more than 3.5 times the pile length (Lp), in the vertical direction and at least 2 times the pile length in the horizontal direction (Fig.…”
Section: Iv2 Numerical Modellingmentioning
confidence: 99%
“…At the neighborhood of the pile-soil interface, the mesh has been refined to avoid the influence of stress concentration on the pile response (Fig. 3) [54], [55].…”
Section: Iv2 Numerical Modellingmentioning
confidence: 99%
“…Moreover, they showed that influence of the soilstructure interaction on the response of the jacket foundation predicts that the flexible foundation model is necessary to estimate loads of the offshore wind turbine structure accurately. Khodair and Abdel-Mohti [7] studied soil-pile interaction for a composite pile using FEM and Finite Difference (FD) method. They used Abaqus and SAP2000 for FEM and LPILE for the FD method.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, several studies have been advocated to the study of soil-pile interaction problems under lateral and axial loads by using simplifying or complex approaches (Taiebat and Carter, 2001, Gu et al, 2016,Khoadir and Mohti, 2014, Chatterjee et al, 2015. Other research groups have focused on the development of simplified expressions for evaluating pile displacements and bending moments along the pile axis (Khodair and Mohti, 2014) by using the subgrade reaction approach (Valsamis 2008, Valsamis et al 2012, Chaloulos et al 2013b. In this approach, the pile is treated as an elastic laterally loaded beam and the soil is idealized as a series of springs.…”
Section: Introductionmentioning
confidence: 99%
“…In this approach, the pile is treated as an elastic laterally loaded beam and the soil is idealized as a series of springs. Nevertheless, the nature of pile-soil interaction is three-dimensional and to complicate further the soil is a nonlinear and anisotropic medium (Khodair and Mohti, 2014). It is common practice to use deep foundations in areas where liquefaction may occur in surface layers.…”
Section: Introductionmentioning
confidence: 99%